Mexican Prickly Poppy: Biology and Control - Brent Sellers (EDIS, 2008)
SS-AGR-304, a 2-page illustrated fact sheet by Brent Sellers, describes biology and control of this annual or biennial member of the poppy family, also known as goatweed, Mexican thistle, prickly poppy and yellow thistle. Published by the UF Department of Agronomy, May 2008.